Green Water Treatment Innovation: Utilization of Avocado Seed Skin and SODIS as an Environmentally Friendly Natural Water Purification Technology - Lismarita, Lismarita; Rahmi, Rauzatur; Mahyuna, Mahyuna; Surya, Erdi (Serambi Journal of Agricultural Technology, 2025)
The availability of clean water is still a serious challenge, especially in rural areas and developing areas. This study aims to examine the innovation of natural-based water purification technology through the use of avocado seed peel as a natural coagulant combined with Solar Water Disinfection (SODIS). The method used is a literature review by analyzing scientific articles in the last ten years related to the effectiveness of avocado seed shells and SODIS in water treatment. The results of the study show that avocado seed shells contain bioactive compounds such as tannins, flavonoids, and polyphenols that function as coagulation and adsorption agents, so that they are able to reduce turbidity, color, and organic and heavy metal content in water. Meanwhile, SODIS technology has been proven to be effective in reducing microbiological contamination, particularly pathogenic bacteria, through the mechanism of UV-A radiation and temperature increase. The combination of these two methods has been proven to complement each other, where pre-treatment with avocado seed peel reduces the turbidity of water so that the penetration of UV rays in the SODIS process is more optimal. The integration of simple, cheap, and environmentally friendly methods has great potential to be applied as an alternative to sustainable clean water supply while supporting the achievement  of the Sustainable Development Goals (SDGs) related to clean water and sanitation.